Hubungan Antara Dukungan Sosial Keluarga dan Self-Love Culture Terhadap Pencegahan Bunuh Diri Remaja - Marthen Preskapu Wela; Antonia Rensiana Reong; Mediatrix Santi Gaharpung (Universitas Kristen Maranatha, 2025)
Adolescents face various psychological challenges that may increase the risk of suicidal behavior. This quantitative descriptive–correlational study aimed to examine the relationships between family social support and self-love culture with suicide prevention among adolescents. Participants were 525 high school students in Maumere, East Nusa Tenggara (233 males, 292 females; M_age = 16.05 years, SD = 1.09). Family social support was measured using the Perceived Social Support-Family Scale (PSS-Fa), self-love culture with an instrument based on Yoon Hong Gyun’s perspective, and suicide prevention with the Reasons for Living Inventory–Adolescent Version (RFL-A). All instruments demonstrated adequate psychometric properties, with Cronbach’s alpha coefficients of 0.78 (family social support), 0.76 (self-love culture), and 0.71 (suicide prevention), and item–total correlation coefficients ranging from 0.235–0.825, 0.231–0.758, and 0.226–0.748, respectively. Data were analyzed using Spearman’s correlation (ρ). The results showed a significant relationship between family social support and suicide prevention (ρ = 0.795; p < 0.001), as well as between self-love culture and suicide prevention (ρ = 0.805; p < 0.001).